Professional Ethics of Advocates in Defending Corporations Involved in Corruption Crimes - Yasinta Diva Negara (Media Hukum Indonesia (MHI), 2026)
Corruption is a crime that can be committed not only by individuals but also by corporations as legal entities. In law enforcement processes, corporations involved in corruption cases retain the right to obtain legal assistance from advocates. This study aims to analyze the role of advocates in defending corporations involved in corruption offenses and to examine the application of professional ethics in carrying out such responsibilities. The research employs a normative legal method through statutory and literature approaches. The findings indicate that advocates play an important role in protecting corporate legal rights and ensuring that judicial proceedings comply with the principle of due process of law. In performing their duties, advocates must uphold integrity, independence, professionalism, and accountability in accordance with the professional code of ethics. They also face various ethical dilemmas, particularly regarding conflicts of interest and the risk of obstruction of justice. Therefore, adherence to professional ethics is essential to maintain a balance between legal defense and anti-corruption efforts.